Tales from a not-so-perfect pet sitter - Russell, Rachel Renée; Russell, Nikki; Russell, Erin (Russell, Rachel Renée. Dork diaries, 2015)
Nikki tries to be a pet sitter, but realizes it's harder work than she thought.